PERAN GURU MATA PELAJARAN AL-QUR’AN HADIST DALAM PENINGKATAN KEMAMPUAN MEMBACA AL-QUR’AN PADA PESERTA DIDIK KELAS VII DI MTS AL-ANSHOR AMBON - Maryam Keliobas (Kuttab: Jurnal Ilmiah Mahasiswa, 2021)
Abstract the results showed that, (1) the role of teachers of hadith subjects in improving the ability to read the Qur'an in grade VII students in MTs Al-Anshor Ambon, implementing several systems including: (a) Implementing Reading the Qur'an before the learning process begins, (b) involving parental participation, (c) providing special or additional tasks, (d) Providing motivation for learners, (e) Utilization of learning resources. (2) several supporting factors, namely (a) the availability of educators, (b) adequate facilities and training, especially Iqro and the Qur'an, (c) the strong willingness of learners to learn to read the Qur'an, (d) the pesantren environment. While the inhibitory factors, namely: (a) Students who have not been able to read the Qur'an smoothly (b) limitations of lesson hours (c) no special program. Keywords: Role of Guru Mapel al-Qur'an Hadith, Improved Reading of the Qur'an Abstrak hasil penelitian menunjukkan bahwa, (1) peran guru mata pelajaran al-Qur’an hadist dalam peningkatan kemampuan membaca al-Qur’an pada peserta didik kelas VII di MTs Al-Anshor Ambon, menerapkan beberapa sistem diantaranya: (a) Menerapkan Membaca al-Qur’an sebelum proses pembelajaran dimulai, (b) melibatkan partisipasi orang tua, (c) memberikan tugas khusus atau tambahan, (d) Memberikan motivasi bagi peserta didik, (e) Pemanfaatan sumber belajar. (2) beberapa faktor pendukung yaitu (a) ketersediaan tenaga pendidik, (b) sarana dan prasaran yang memadai khususnya Iqro dan al-Qur’an, (c) kemauan yang kuat dari peserta didik untuk belajar membaca al-Qur’an, (d) lingkungan pesantren. Sedangkan faktor penghambat, yaitu: (a) Peserta didik yang belum bisa membaca al-Qur’an dengan lancar (b) keterbatasan jam pelajaran (c) tidak ada program khusus. Kata Kunci: Peran Guru Mapel al-Qur’an Hadits, Peningkatan Membaca al-Qur’an